Hallmarks of perineural invasion in pancreatic ductal adenocarcinoma: new biological dimensions - Sun, Yaquan; Jiang, Wei; Liao, Xiang; Wang, Dongqing (Frontiers in Oncology, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is an aggressive malignant tumor with a high metastatic potential. Perineural invasion (PNI) occurs in the early stages of PDAC with a high incidence rate and is directly associated with a poor prognosis. It involves close interaction among PDAC cells, nerves and the tumor microenvironment. In this review, we detailed discuss PNI-related pain, six specific steps of PNI, and treatment of PDAC with PNI and emphasize the importance of novel technologies for further investigation.